New Yeast Species, Malassezia dermatis, Isolated from Patients with Atopic Dermatitis - Sugita, Takashi (American Society for Microbiology, 2002)
Malassezia species are considered to be one of the exacerbating factors in atopic dermatitis (AD). During examination of the cutaneous colonization of Malassezia species in AD patients, we found a new species on the surface of the patients' skin. Analysis of ribosomal DNA sequences suggested that the isolates belonged to the genus Malassezia. They did not grow in Sabouraud dextrose agar but utilized specific concentrations of Tween 20, 40, 60, and 80 as a lipid source. Thus, we concluded that our isolates were new members of the genus Malassezia and propose the name Malassezia dermatis sp. nov. for these isolates.